Characteristics of Functional Constipation among Kindergarten Students in Kecamatan Jatinangor, West Java, Indonesia - Giovanni, Livia; Ermaya, Yudith Setiati; Hafsah, Tisnasari (Althea Medical Journal, 2018)
Background: Functional constipation can occur in children and affect their quality of life, but there is still lack of awareness and inability to provide proper management. Therefore, early detection is important. The aim of this study was to identify the prevalence of functional constipation among kindergarten students and its risks.Methods: A quantitative descriptive study was conducted from April to May 2017 on kindergarten students in Kecamatan Jatinangor, West Java, Indonesia by using questionnaires for their parents. In total, 149 parents joined the study.Â  The questionnaire was made based on the Rome IV Criteria with additional questions for the studentâs characteristics comprised of sex, prematurity, allergy, family history of constipation, dietary fiber consumption, and parentsâ education level. Descriptive analyses were conducted.Results: The prevalence of functional constipation among the students was 8.7% with the most frequent complaints were retentive posturing (76.9%), hard stool consistency (38.5%), and history of obstructing toilet by stool (38.5%). Characteristics of children with functional constipation were prematurity (15.4%), history of allergy (15.4%), low dietary fiber intake (from fruits, 69.2%, vegetables 84.6%, seeds 100%), and non-university educated parents (father 76.9%, mother 84.6%).Conclusions: Constipation among kindergarten students in Jatinangor is 8.7%, while the most apparent characteristics in constipated children is low dietary fiber intake.Â